Evolution of Canadian Poet Rupi Kaur (Literary Voice, 2023)
Rupi Kaur is an Indian-Canadian poet and artist who had immigrated to Canada with her parents as a child. She is an alumni of University of Waterloo (Canada). She stormed the world poetry scene and carved out a niche for herself among millions of readers with self-published first poetry collection, Milk and Honey in 2014, followed by The Sun and Her Flowers in 2017, both bestsellers across the world, “sold more than 11 million copies and translated into over forty three languages.” Her third poetry collection, Homebody, was released in 2020. In 2022 she released her 4th book Healing Through Words which chronicles a journey of guided writing exercises to help the reader explore their creativity. The present article puts in sharp focus her evolution as a poet whose oeuvre is informed by feministic/human concerns.
Keywords: immigrant, trauma, diversity, resilience, domestic violence, instapoets.